2010
DOI: 10.5194/nhess-10-2269-2010
|View full text |Cite
|
Sign up to set email alerts
|

Mid-level synoptic analysis of flood-generating systems in South-west of Iran (case study: Dalaki watershed river basin)

Abstract: Abstract. Flood is known as one of the most distractive natural disaster worldwide. Therefore, its prediction is of great importance from the socio-economical point of view. Despite the great improvement in computational techniques and numerical weather prediction approaches, so far, in Iran, an acceptable flood prediction method has not yet been introduced. The main aim of this study is to recognize and classify the patterns of synoptic systems leading to torrential rainfalls in a watershed basin located in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…[48] Our study underscores that the intensified AA and associated moisture transport not only characterize the December 1993 event [Ziv et al, 2005] and the Jeddah 2009 event [Haggag and El-Badry, 2013], but are relevant for all analyzed Levant ARSTs (Figure 8). Apart from the ARST, the AA and associated moisture transport are also involved in precipitation and floods in Iran [Farajzadeh et al, 2007;Sabziparvar et al, 2010;Raziei et al, 2012]. The latter study found the AA to induce lower tropospheric moisture transport from tropical water bodies (Arabian Sea, Oman Sea, Persian Gulf, Red Sea, and northern Indian Ocean) into cyclonic systems near Iran.…”
Section: Unified Concept Of the Arst Dynamicsmentioning
confidence: 99%
“…[48] Our study underscores that the intensified AA and associated moisture transport not only characterize the December 1993 event [Ziv et al, 2005] and the Jeddah 2009 event [Haggag and El-Badry, 2013], but are relevant for all analyzed Levant ARSTs (Figure 8). Apart from the ARST, the AA and associated moisture transport are also involved in precipitation and floods in Iran [Farajzadeh et al, 2007;Sabziparvar et al, 2010;Raziei et al, 2012]. The latter study found the AA to induce lower tropospheric moisture transport from tropical water bodies (Arabian Sea, Oman Sea, Persian Gulf, Red Sea, and northern Indian Ocean) into cyclonic systems near Iran.…”
Section: Unified Concept Of the Arst Dynamicsmentioning
confidence: 99%
“…Iran, which is located in the mid-latitude belt of arid and semiarid regions of the Earth, is affected by extreme precipitation events. Due to specific topographic, land cover, and soil conditions in the country, heavy precipitation cannot penetrate into the ground, leading to sudden runoff flows and disastrous floods in vulnerable areas (Sabziparvar et al, 2010). For that reason, flash floods have increased during recent years in the country (Roughani et al, 2007;DOE, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the patterns that do not form a cluster can be recognized too. Moran's I is calculated through equation (6) or equation (7). Z score is calculated by equation (8).…”
Section: Methodsmentioning
confidence: 99%
“…understorms may be the result of severe gradient between two systems [7,8]. A number of studies have indicated that height plays a significant role in the onset and evolution of storms [9].…”
Section: Introductionmentioning
confidence: 99%